Paul Feyerabend: realist and anti-realist - Eder Ricardo (2023)
Intensely discussed in the philosophy of science in the 20th and 21st centuries, the themes of realism and anti-realism pervade Feyerabend’s work. However, discerning the author’s position on these subjects poses a problem for scholars. One sign of this is that they attribute to Feyerabend the adherence to (or the rejection of) different conceptions of realism and anti-realism. Despite the divergences, however, scholars approach the topic in a similar way, detecting elements of Feyerabend’s realist and anti-realist positions that are incompatible with each other and that follow one another in the course of his work. Although such studies are of great value, we propose to explore another approach, which also seems pertinent. Examining Feyerabend’s writings, we seek to discern conditions that make it possible for the author to assume, without contradiction, realist and anti-realist positions. Finally, we seek to infer from Feyerabend’s conception of science features of the realism prescribed by the author as well as features of the realism proscribed by him.